2022
DOI: 10.3389/fendo.2022.876028
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Its Impact on Adverse In-Hospital Outcomes in Hospitalized Patients With COVID-19

Abstract: BackgroundAn increasing level of evidence suggests that obesity not only is a major risk factor for cardiovascular diseases (CVDs) but also has adverse outcomes during COVID-19 infection.MethodsWe used the German nationwide inpatient sample to analyze all hospitalized patients with confirmed COVID-19 diagnosis in Germany from January to December 2020 and stratified them for diagnosed obesity. Obesity was defined as body mass index ≥30 kg/m2 according to the WHO. The impact of obesity on in-hospital case fatali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 76 publications
(148 reference statements)
1
24
0
Order By: Relevance
“…Another key factor is the change regarding the focus of the health care service [ 14 , 15 ]. In order to encounter the consequences caused by the COVID-19 pandemic, the health care systems have changed the organization and management of the health institutions with focus on the COVID-19 pandemic [ 4 , 14 , 37 ]. This changed organization had an important impact regarding the diagnosis and treatment of patients with other prevalent, acute or chronic diseases that carry an increased risk for adverse outcomes with and without co-prevalence of COVID-19, but especially in patients with COVID-19 infection, in whom these other acute and chronic diseases might be overlooked, considered to be unimportant at this time or be unnoticed [ 4 , 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another key factor is the change regarding the focus of the health care service [ 14 , 15 ]. In order to encounter the consequences caused by the COVID-19 pandemic, the health care systems have changed the organization and management of the health institutions with focus on the COVID-19 pandemic [ 4 , 14 , 37 ]. This changed organization had an important impact regarding the diagnosis and treatment of patients with other prevalent, acute or chronic diseases that carry an increased risk for adverse outcomes with and without co-prevalence of COVID-19, but especially in patients with COVID-19 infection, in whom these other acute and chronic diseases might be overlooked, considered to be unimportant at this time or be unnoticed [ 4 , 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…During December 2019, pneumonia cases caused by a previously unknown virus occurred in China [ 1 , 2 , 3 , 4 ]. In Germany, the first patient with SARS-CoV-2 infection was identified at the end of January 2020 in Bavaria [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not able to clearly distinguish patients with preserved, mid-range and reduced ejection fraction. Body mass index as important characteristic of heart failure population ( 30 ) and negative prognostic factor of COVID-19 ( 31 ) was not known and not included in the analysis. It was also hypothesized that physical activity and air pollution could play a role in the spread of the virus ( 32 , 33 ), our data do not allow us identifying patients who live in geographic areas with increased air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HTN and COVID-19 is not necessarily causal. HTN occurs more commonly in the elderly and in patients with other comorbidities, including increased adiposity (since fat cells have higher concentration of ACE-2 receptors than the lungs, worsening COVID-19 prognosis [15,16]), all of which are associated with increased risk of severe COVID-19 [17]. In an observational study of 12 594 patients conducted in New York City, a history of HTN was reported 34.6% [18].…”
Section: Hypertension and Coronavirus Disease 2019mentioning
confidence: 99%